Coordinated regulation of water use-efficiency-cost in a winter wheat-summer maize rotation system and optimization of water allocation strategies - Li Zhao; Congying Han; Yinong Li; Baozhong Zhang; Yulu Zheng; Jiabing Cai (Agricultural Water Management)
In the North China Plain, the winter wheat-summer maize rotation system faces challenges due to the mismatch between precipitation patterns and crop water demands, leading to groundwater over-exploitation and low irrigation efficiency. This study, based on a 2023–2024 field irrigation experiment and the simulation of dynamic field water cycles, examines how water allocation affects crop growth and yield. A multi-objective nonlinear programming model was developed, incorporating triangular fuzzy numbers, accuracy functions, and credibility constraints, to balance actual yield (AY), irrigation water productivity (IWP), and total cost (TC). Results show that water allocation significantly influences crop yield, and a trade-off exists among yield, irrigation water productivity, and cost. As the credibility level increases, cost tends to stabilize, whereas yield and irrigation water productivity show greater variability. Lower credibility values help improve the overall satisfaction of multiple objectives. The optimized scheme increased crop yield by 4.02 %, improved irrigation water productivity by 5.84 %, reduced costs by 7.17 %, enhanced total water productivity by 3.17 %, and cut annual irrigation volume by 15.69 %.